Evaluation of Existing Pedagogy of Teaching in the Private Universities of Bangladesh: An Overview - Ali, Yeakub (International Journal of Language Education, 2019)
Abstract: Higher education is acknowledged today as a capital investment and is of paramount importance for economic and social development of a country (Barnet, 1990). Some specialists called attention that the present higher education system employs rote memorization approach rather than critical thinking by students. It is, therefore, needed not only to relook at our pedagogy of teaching and learning principles including methods but also to revitalize the higher education system. Although Bangladesh has had a long history of university teaching, pedagogy has hardly entered the imagination of university educators. Today’s teachers are yesterday’s students, with each generation being groomed in the same cultural patterns of learning that are continually repeated without examination. Pedagogy teaches teachers how to teach, so that they may effectively teach students how to learn; it offers important training for teachers to transform students from mere parrots of information into challengers of and innovators of knowledge. Earlier public sector had monopoly in the tertiary level of education. In 1992 private sector started its function. Within a short span of time more than ninety private universities have started their action. The Emergence and the growth of the private universities in Bangladesh have taken a phenomenal shape in recent years. However, the private universities are playing an important role in spreading the opportunities of higher education in our country. But in recent years a widespread allegations were raised against PUs that some are selling certificates, easy-to-get degrees, very poor teaching qualities, poor infrastructure, high tuition fees, etc. In this context this study is an initiative to explore the education quality (EQ) of PUs that is offered by them. This paper analyses the existing pedagogy, teaching style, quality education, capability of teachers to teach students and infrastructure of the Private University of Bangladesh.